Pandangan Lembaga Keagamaan Kota Medan Tentang Ajaran Islam Salafi dan Kristen Kharismatik - Nurhaliza, Nurhaliza; Harahap, H. Indra; Fitriani, Fitriani (ANWARUL, 2024)
This research aims to describe what is meant by Salafi Islam and Christian Christianity and what the MUI views regarding the teachings of Charismatic Islam. This research is a type of library research. This research uses a phenomenological approach with comparative theory. The phenomenological approach seeks to let reality reveal itself naturally. The data sources for this research are library materials in the form of books, writings, encyclopedias, journals and other sources relevant to this topic. The results of this research show that Salafi and Charismatic Christian teachings are two religious sects that have quite striking differences in beliefs, practices and approaches. theological. According to the view of Islamic scholars, Salafis prioritize a literal and literal understanding of the Qur'an, emphasize monotheism, and reject the practice of heresy. They try to maintain Islamic practices which they believe are in accordance with the initial teachings. On the other hand, Charismatic Christians prioritize spiritual experiences and the gifts of the Holy Spirit in Christian life. They believe that the Holy Spirit is active in providing gifts such as speaking in tongues, spiritual healing, and other charismatic experiences.